Electrochemical and Electronic Devices
Patent Information
- Application Number
- JP2024547757
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-11-01
- Filing Date
- 2023-10-09
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-10-09
Smart Images

Figure 2025506194000001_ABST
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to a Chinese patent application bearing application number 202211353337.1, filed on November 1, 2022, and entitled "Electrochemical Device and Electronic Device," the entire contents of which are incorporated herein by reference.
[0002] Technical Field The present invention relates to the technical field of electrochemical devices, in particular electrochemical and electronic devices. [Background technology]
[0003] Devices such as consumer electronics, electric transportation vehicles and the like have become an indispensable part of people's lives, and these devices require electrochemical devices to supply electrical energy, thus driving the rapid development of electrochemical devices represented by lithium-ion secondary batteries.
[0004] However, in the related art, the electrochemical device has poor high-temperature cycle characteristics, which limits its application to some devices. Summary of the Invention
[0005] The present invention provides an electrochemical device and an electronic device, the electrochemical device having good high temperature cycling properties.
[0006] In a first aspect, an embodiment of the present invention provides an electrochemical device, the electrochemical device including a positive electrode piece, the positive electrode piece including a positive electrode current collector and a positive electrode active material layer provided on one or both sides of the positive electrode current collector, the positive electrode active material layer including a positive electrode active material, wherein the thickness H of the positive electrode active material layer on one side is 1 D of the positive electrode active material v The ratio of 99 is 0.5≦D v 99 / H 1 ≦0.9. The diameter D of the bright spot on the surface of the positive electrode active material layer is measured by a scanning electron microscope. 0agglomerated regions having a size of 20 μm or larger than 20 μm are observed, and the number density of the agglomerated regions per unit area on the surface of the positive electrode active material layer is 5 pieces / cm 2 or 5 pieces / cm 2 Less than.
[0007] In the electrochemical device provided by the embodiment of the present invention, the thickness H of the positive electrode active material layer on one side 1 D of the positive electrode active material v The ratio of 99 is 0.5≦D v 99 / H 1 ≦0.9. This makes it possible to make the positive electrode piece thinner, reduce the ion transport path, further reduce the ion polarization, and further reduce the resistance of the electrochemical device. In addition, the diameter D of the bright spot on the surface of the positive electrode active material layer observed by a scanning electron microscope 0 or the number density per unit area on the surface of the positive electrode active material layer of the agglomerated region is 5 particles / cm 2 or 5 pieces / cm 2 The smaller size reduces the number of positive electrode active materials crushed during the roll-press process of the positive electrode active material layer, which helps improve the high-temperature cycle characteristics of the electrochemical device.
[0008] According to any one of the above embodiments of the first aspect of the present invention, the positive electrode active material D v 99 is 15μm≦D v 99≦30μm, and the thickness H of the positive electrode active material layer on one side is 1 10μm≦H 1 Meets ≦35μm.
[0009] According to any one of the above embodiments of the first aspect of the present invention, the positive electrode active material D v D of the positive electrode active material to 10 v The ratio of 50 is 1.0≦D v 50 / D v Satisfy 10≦2.5.
[0010] According to any one of the above embodiments of the first aspect of the present invention, the positive electrode active material D v D of the positive electrode active material to 10v The ratio of 50 is 1.0≦D v 50 / D v Satisfy 10≦2.0.
[0011] According to any one of the above embodiments of the first aspect of the present invention, the positive electrode active material includes a nickel-cobalt-manganese ternary material.
[0012] According to any one of the above embodiments of the first aspect of the present invention, the mole fraction of nickel in the nickel-cobalt-manganese ternary material is 60% or greater than 60%.
[0013] According to any one of the above embodiments of the first aspect of the present invention, the thickness H of the positive electrode current collector 2 teeth, I)0.3≦H 2 / D v 99≦1, II) 1≦H 1 / H 2 ≦4, III) 7μm≦H 2 ≦20μm, Satisfy at least one of the following:
[0014] According to any one of the above embodiments of the first aspect of the present invention, the thickness H of the positive electrode current collector 2 , 8μm≦H 2 Meets ≦12μm.
[0015] According to any one of the above-mentioned embodiments of the first aspect of the present invention, the areal density of the positive electrode active material layer is 80 mg / 1540.25 mm 2 ~180mg / 1540.25mm 2 It is.
[0016] According to any one of the above-described embodiments of the first aspect of the present invention, the compressed density of the positive electrode active material layer is 3.3 g / cm 3 ~3.7g / cm 3 It is.
[0017] According to any one of the above-described embodiments of the first aspect of the present invention, the compressed density of the positive electrode active material layer is 3.5 g / cm 3 ~3.65g / cm 3 It is.
[0018] According to any one of the above embodiments of the first aspect of the present invention, the positive electrode active material layer further comprises a binder, and the binder has a characteristic peak in the corresponding Fourier transform infrared spectrum: 1684 cm -1 has.
[0019] According to any one of the above embodiments of the first aspect of the present invention, the binder comprises a polyvinylidene fluoride copolymer.
[0020] According to any one of the above embodiments of the first aspect of the present invention, the binder has a structural formula of formula (A): (VDF)m(TFE)n(HFP)r(PVP)x (A) In formula (A), VDF is a structural unit of vinylidene fluoride, TFE is a structural unit of tetrafluoroethylene, HFP is a structural unit of hexafluoropropylene, PVP is a structural unit of polyvinylpyrrolidone, and m, n, r, and x satisfy 0.35≦m≦1, 0≦n≦0.4, 0≦r≦0.2, 0≦x≦0.2, and m+n+r+x=1.
[0021] In a second aspect, embodiments of the present invention provide an electronic device comprising an electrochemical device according to any embodiment of the first aspect of the present invention.
[0022] The above description is only an outline of the technical solution of the present invention. In order to more clearly understand the technical solutions of the present invention and to implement them in accordance with the content of the specification, and to more clearly understand the above and other objectives, features and advantages of the present invention, specific embodiments of the present invention are described below. [Brief description of the drawings]
[0023] Various other advantages and benefits will become apparent to those skilled in the art upon reading the following detailed description of the embodiments. The drawings are only for purposes of illustrating some embodiments and should not be construed as limiting the invention. In the drawings, the same elements are designated by the same reference numerals throughout. [Figure 1] FIG. 1 is a structural schematic diagram of an electrochemical device provided by an embodiment of the present invention. [Diagram 2] FIG. 2 is an exploded structural schematic diagram of the electrochemical device shown in FIG. [Diagram 3] FIG. 3 is a SEM image of a positive electrode piece in the electrochemical device provided by Example 1 of the present invention. [Figure 4] FIG. 4 is a SEM image of a positive electrode piece in the electrochemical device provided by Comparative Example 1 of the present invention. [Explanation of symbols]
[0024] 5-electrochemical device, 51-case, 52-electrode assembly, 53-top cover assembly. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0025] The following describes in detail the embodiments of the technical solution of the present invention with reference to the drawings. The following embodiments are only used to more clearly explain the technical solution of the present invention, and are therefore merely illustrative and do not limit the protection scope of the present invention.
[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the present invention belongs. The terms used herein are intended only to describe specific examples and are not intended to limit the present invention. The terms "comprises" and "has" and any variations thereof in the present specification and claims and the above description of the drawings are intended to include non-exclusive inclusions.
[0027] In the description of the embodiments of the present invention, the terms "first", "second", etc. are used only to distinguish different objects, and should not be understood as indicating or implying relative importance, or the number, particular order, or primary-secondary relationship of the technical features shown. In the description of the embodiments of the present invention, the meaning of "plurality" means two or more, unless otherwise clearly limited.
[0028] In this specification, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with the embodiment may be included in at least one embodiment of the present invention. The appearance of this phrase in various places in the specification does not necessarily refer to all the same embodiment, nor does it refer to separate or alternative embodiments that are mutually exclusive with other embodiments. Those skilled in the art will explicitly and implicitly understand that the embodiments described herein can be combined with other embodiments.
[0029] In the description of the embodiments of the present invention, the term "and / or" simply describes a relation between related objects and indicates that three relations can exist, for example, "A and / or B" can indicate three situations: A exists alone, A and B exist simultaneously, and B exists alone. Note that the character " / " in this specification generally indicates that the related objects before and after it have an "or" relationship.
[0030] In describing the embodiments of the present invention, unless otherwise specified, "more than" and "less than" include the reference quantity, and "multiple types" and "multiple pieces" in "one type or multiple types" and "one or multiple" mean two types (pieces) or more.
[0031] Groupings of alternative elements or embodiments disclosed herein should not be construed as limitations. Each group member may be taken alone and claimed alone, or taken and claimed in any combination with other members of the group or other elements found herein. It is contemplated that one or more members of a group may be included in or deleted from a group for reasons of convenience and / or patentability. When any such inclusion or deletion occurs, the specification is deemed to contain the modified group, and thus fulfills the written description of all Markush groups used in the claims.
[0032] It is obvious to those skilled in the art that various modifications and changes can be made in the present invention without departing from the scope of protection of the present invention. Therefore, the present invention is intended to cover the modifications and changes of the present invention that fall within the scope of the corresponding claims (scope of protection) and their equivalents. In addition, the embodiments of the present invention can be combined with each other as long as they are not inconsistent.
[0033] Before describing the scope of protection according to the embodiments of the present invention, problems existing in the related art of the present invention will be specifically described first in order to facilitate understanding of the embodiments of the present invention.
[0034] Electrochemical devices, such as lithium-ion secondary batteries, have characteristics such as high energy density, good cycle characteristics, and rechargeability, and are therefore widely used in consumer electronic devices, electric transportation vehicles, and other devices. With the rapid development of secondary battery technology, the development of rapid charge and discharge technology has been promoted, and lithium-ion secondary batteries that support rapid charge and discharge have become one of the most popular electrochemical devices on the market.
[0035] In the related art, a lithium ion secondary battery generates a large amount of heat during high-rate charging and discharging, which increases the temperature of the lithium ion secondary battery and makes it more likely to cause polarization. In order to reduce the polarization of a lithium ion secondary battery, the thickness of the pole piece can be reduced to shorten the ion transport path. However, due to the reduction in the thickness of the pole piece, when the aggregated slurry is applied to the surface, protrusions are formed, and the active material in the protrusions is easily crushed during the roll press process. During the high-rate charging and discharging process, the temperature of the lithium ion secondary battery increases, which deteriorates the cycle characteristics of the lithium ion secondary battery.
[0036] In view of this, embodiments of the present invention provide electrochemical and electronic devices, where the electrochemical device has good high temperature cycling characteristics.
[0037] In the present invention, the electrochemical device includes any device in which an electrochemical reaction occurs, and specific examples thereof include all kinds of primary batteries, secondary batteries, fuel cells, solar cells, and capacitors. Exemplarily, the electrochemical device is a lithium secondary battery, which may include a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery, and a lithium ion polymer secondary battery.
[0038] Electrochemical Equipment An embodiment of the present invention provides an electrochemical device including a positive electrode piece, the positive electrode piece including a positive electrode current collector and a positive electrode active material layer provided on one or both sides of the positive electrode current collector, the positive electrode active material layer including a positive electrode active material, wherein the thickness H of the positive electrode active material layer on one side is 1 D of the positive electrode active material v The ratio of 99 is 0.5≦D v 99 / H 1 ≦0.9. The diameter D of the bright spot on the surface of the positive electrode active material layer is measured by a scanning electron microscope. 0 agglomerated regions having a size of 20 μm or larger than 20 μm are observed, and the number density of the agglomerated regions per unit area on the surface of the positive electrode active material layer is 5 pieces / cm 2 or 5 pieces / cm 2 Less than.
[0039] In the present invention, the protrusions on the surface of the pole pieces have a diameter D after roll pressing. 0 The number of agglomerated regions per unit area is reduced by reducing the number of protrusions on the surface of the pole pieces, thereby improving the uniformity of the surface of the pole pieces and improving the problem of deterioration of cycle characteristics caused by the fracture of the protrusions during the roll pressing process of the pole pieces. The smaller the agglomerated region, the fewer the protrusions on the surface of the pole pieces before roll pressing, and therefore the smaller the agglomerated region of the pole pieces after roll pressing, the better.
[0040] D v 99 represents the particle size at which the cumulative volume from the small particle size side is 90% in the volume-based particle size distribution.
[0041] Diameter D 0 refers to the largest measurable distance in an area when it does not form a clearly defined shape.
[0042] The term "aggregated region" refers to a region formed after roll pressing in which aggregated particles in a positive electrode slurry that forms a positive electrode active material layer are applied to the surface of a positive electrode current collector and then protrude from the surface of the formed positive electrode active material layer.
[0043] In the electrochemical device provided by the embodiment of the present invention, the thickness H of the positive electrode active material layer on one side 1 D of the positive electrode active material v The ratio of 99 is 0.5≦D v 99 / H 1 ≦0.9, thus making the positive electrode piece thinner, reducing the ion transport path, further reducing the ion polarization, and further reducing the resistance of the electrochemical device. In addition, the diameter D of the bright spot on the surface of the positive electrode active material layer observed by a scanning electron microscope 0 or the number density per unit area on the surface of the positive electrode active material layer of the agglomerated region is 5 particles / cm 2 or 5 pieces / cm 2The smaller size reduces the number of positive electrode active materials crushed during the roll-press process of the positive electrode active material layer, which helps improve the high-temperature cycle characteristics of the electrochemical device.
[0044] In the embodiment of the present invention, the positive electrode active material D v 99 and the thickness H of the positive electrode active material layer on one side 1 By rationally combining the above, the positive electrode pieces can be made thinner and the defects generated during the processing can be reduced, and the occurrence of fracture of the positive electrode active material can also be reduced.
[0045] In some embodiments of the present invention, the positive electrode active material D v 99 is 15μm≦D v 99≦30μm, and the thickness H of the positive electrode active material layer on one side is 1 10μm≦H 1 Meets ≦35μm.
[0046] In the above examples, the positive electrode active material D v 99 and the thickness H of the positive electrode active material layer on one side 1 By rationally combining these, defects such as scratches during processing of the positive electrode active material layer can be reduced, and further, the number of positive electrode active materials crushed during the roll press process can be reduced, which is helpful in improving the high-temperature cycle characteristics of the electrochemical device.
[0047] In some instances, the D of the positive electrode active material v 99 may be, but is not limited to, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm, 25 μm, 26 μm, 27 μm, 28 μm, 29 μm, or 30 μm. 1may be, but is not limited to, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm, 25 μm, 26 μm, 27 μm, 28 μm, 29 μm, 30 μm, 31 μm, 32 μm, 33 μm, 34 μm, or 35 μm.
[0048] In addition, by setting the volumetric particle size distribution of other particles of the positive electrode active material within an appropriate range, the occurrence of crushing of the positive electrode active material can be reduced, and electrochemistry can be reduced to improve the energy density of the electrochemical device.
[0049] In some embodiments of the present invention, the positive electrode active material D v D of the positive electrode active material to 10 v The ratio of 50 is 1.0≦D v 50 / D v Satisfy 10≦2.5.
[0050] D v 50 represents the particle size at which the cumulative volume is 50% from the small particle size side in the volume-based particle size distribution.
[0051] D v The number 10 indicates the particle size at which the cumulative volume from the small particle size side is 10% in the volume-based particle size distribution.
[0052] In the above examples, the positive electrode active material D v D for 10 v When the ratio of 50 satisfies the above relationship, the crushing of the positive electrode active material can be reduced, and the resistance of the positive electrode pieces and the expansion rate of the electrochemical device can be reduced, thereby further improving the high-temperature cycle characteristics of the electrochemical device.
[0053] In some embodiments of the present invention, the positive electrode active material D v D of the positive electrode active material to 10 v The ratio of 50 is 1.0≦D v 50 / D v Satisfy 10≦2.0.
[0054] In the above examples, the positive electrode active material D v D for 10 v When the ratio of 1 to 50 satisfies the above relationship, the crushing of the positive electrode active material can be further reduced, and the high-temperature cycle characteristics of the electrochemical device can be improved.
[0055] In some cases, the D of the positive electrode active material v Diameter D of the positive electrode active material relative to 10 v The ratio of 50 may be, but is not limited to, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, or 2.5.
[0056] In some embodiments of the present invention, the thickness of the positive electrode current collector also affects the packing density and processing of the positive electrode active material layer. 2 teeth, I)0.3≦H 2 / D v Satisfying 99≦1, II) 1≦H 1 / H 2 ≦4 and III) 7μm≦H 2 ≦20μm, Satisfy at least one of the following:
[0057] In the above example, the thickness H of the positive electrode current collector 2 , H 2 / D v 99 and H 1 / H 2 When the ratio is within an appropriate range, the compression density of the positive electrode active material layer can be further improved, and the occurrence of breakage of the positive electrode pieces due to roll pressing and overpressure damage of the positive electrode active material can be reduced, the resistance of the positive electrode pieces and the expansion rate of the electrochemical device can be reduced, and the high-temperature cycle characteristics of the electrochemical device can be improved.
[0058] In some embodiments of the present invention, the thickness H of the positive electrode current collector 2may be in the range of 8 μm to 12 μm, and the thickness H of the positive electrode current collector 2 Within this range, the compressed density of the positive electrode active material can be further improved, and the resistance of the positive electrode pieces can be reduced, thereby improving the high-temperature cycle characteristics of the electrochemical device.
[0059] In some instances, the D of the positive electrode active material v Thickness H of the positive electrode current collector relative to 99 2 The ratio may be, but is not limited to, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, or 1. The thickness H of the positive electrode current collector 2 Thickness H of the positive electrode active material layer 1 The ratio of may be, but is not limited to, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, or 4.0. 2 may be, but is not limited to, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, or 20 μm.
[0060] The present invention does not particularly limit the material of the positive electrode current collector, and the positive electrode current collector may be a metal foil or a porous metal plate, for example, a foil or a porous plate of a metal such as aluminum, copper, nickel, titanium, iron, etc., or an alloy thereof. In some embodiments of the present invention, the positive electrode current collector is an aluminum foil.
[0061] In some embodiments of the present invention, the positive electrode active material layer has a compressed density of 3.3 g / cm 3 ~3.7g / cm 3 It is.
[0062] In the above examples, by setting the compressed density of the positive electrode active material layer within the above range, it is possible to contribute to improving the high-temperature cycle characteristics of the electrochemical device.
[0063] In another embodiment of the present invention, the compressed density of the positive electrode active material layer is 3.5 g / cm 3 ~3.65g / cm 3 It is.
[0064] In some examples, the compressed density of the positive electrode active material layer is 3.3 g / cm 3 , 3.31g / cm 3 , 3.32g / cm 3 , 3.33g / cm 3 , 3.34g / cm 3 , 3.35g / cm 3 , 3.36g / cm 3 , 3.36g / cm 3 , 3.38g / cm 3 , 3.39g / cm 3 , 3.40g / cm 3 , 3.41g / cm 3 , 3.42g / cm 3 , 3.43g / cm 3 , 3.44g / cm 3 , 3.45g / cm 3 , 3.46g / cm 3 , 3.47g / cm 3 , 3.48g / cm 3 , 3.49g / cm 3 , 3.50g / cm 3 , 3.51g / cm 3 , 3.52g / cm 3 , 3.53g / cm 3 , 3.54g / cm 3 , 3.55g / cm 3 , 3.56g / cm 3 , 3.57g / cm 3 , 3.58g / cm 3 , 3.59g / cm 3 , or 3.6 g / cm 3 It may be, but is not limited to, these.
[0065] The positive electrode active material can directly affect the energy density and cycle characteristics of the electrochemical device, and therefore, in some embodiments of the present invention, the positive electrode active material comprises a nickel-cobalt-manganese ternary material, which can contribute to improving the energy density and cycle characteristics of the electrochemical device.
[0066] The nickel cobalt manganese ternary material may be a ternary structural material such as NCM811, NCM622, NCM613, NCM523, NCM111, etc.
[0067] In NCM811, N represents nickel, C represents cobalt, M represents manganese, and 811 represents the mole ratio of nickel, cobalt, and manganese in the ternary material, that is, the mole ratio of nickel element:cobalt element:manganese element is 8:1:1, and at this time, the mole ratio of nickel in the nickel-cobalt-manganese ternary material is 80% of the total mole ratio of nickel, cobalt, and manganese. In NCM523, the mole ratio of nickel element:cobalt element:manganese element is 5:2:3, and the mole ratio of nickel in the nickel-cobalt-manganese ternary material is 50% of the total mole ratio of nickel.
[0068] In some embodiments of the present invention, the moles of nickel in the nickel-cobalt-manganese ternary material are equal to or greater than 60% of the total moles of nickel, cobalt and manganese.
[0069] In another embodiment of the present invention, the positive electrode active material may further include at least one of an olivine structure material, such as lithium manganese iron phosphate, lithium iron phosphate, lithium manganese phosphate, and a lithium cobalt oxide material, a lithium manganate material, other metal oxides capable of releasing lithium, and the like.
[0070] The positive electrode active material layer is formed by applying a positive electrode slurry to the surface of a positive electrode current collector, and the surface density of the positive electrode active material layer affects to some extent the energy density and cycle characteristics of the electrochemical device.
[0071] In the present invention, the areal density means the mass of the positive electrode active material per unit area.
[0072] In some embodiments of the present invention, the areal density of the positive electrode active material layer is 80 mg / 1540.25 mm 2 ~180mg / 1540.25mm 2 It is.
[0073] In the above examples, setting the areal density of the positive electrode active material layer within the above appropriate range contributes to uniformly dispersing each component in the positive electrode active material layer on the surface of the positive electrode current collector, reduces gel formation, and is advantageous for improving the high-temperature cycle characteristics of the electrochemical device.
[0074] In some examples, the areal density of the positive electrode active material layer is 80 mg / 1540.25 mm 2 ~90mg / 1540.25mm 2 , 91mg / 1540.25mm 2 ~100mg / 1540.25mm 2 , 101mg / 1540.25mm 2 ~110mg / 1540.25mm 2 , 111mg / 1540.25mm 2 ~120mg / 1540.25mm 2 , 121mg / 1540.25mm 2 ~130mg / 1540.25mm 2 , 131mg / 1540.25mm 2 ~140mg / 1540.25mm 2 , 141mg / 1540.25mm 2 ~150mg / 1540.25mm 2 , 151mg / 1540.25mm 2 ~160mg / 1540.25mm 2 , 161mg / 1540.25mm 2~170mg / 1540.25mm 2 , or 171 mg / 1540.25 mm 2 ~180mg / 1540.25mm 2 It may be, but is not limited to, these.
[0075] In some embodiments of the present invention, the positive electrode active material layer further comprises a binder, and the binder has a characteristic peak in the Fourier transform infrared spectrum: 1684 cm -1 has.
[0076] In the above embodiment, the binder can improve the stability of the slurry viscosity and further reduce the formation of gel, particularly in the positive electrode active material layer of the high nickel positive electrode active material, thereby contributing to the formation of a uniform and thin positive electrode active material layer.
[0077] In some embodiments of the present invention, the binder comprises a polyvinylidene fluoride copolymer.
[0078] In some embodiments of the present invention, the binder has a structural formula of Formula (A): (VDF)m(TFE)n(HFP)r(PVP)x (A) In formula (A), VDF is a structural unit of vinylidene fluoride, TFE is a structural unit of tetrafluoroethylene, HFP is a structural unit of hexafluoropropylene, PVP is a structural unit of polyvinylpyrrolidone, and m, n, r, and x satisfy 0.35≦m≦1, 0≦n≦0.4, 0≦r≦0.2, 0≦x≦0.2, and m+n+r+x=1.
[0079] In the above embodiment, the binder has the structural formula of formula (A), which can contribute to the dispersion of the slurry components such as the conductive agent and the positive electrode active material, inhibit the formation of gel, and further reduce the occurrence of abnormal aggregation between the components, reduce the number of protrusions on the surface of the pole pieces, and also reduce the number of aggregation areas where the protrusions are formed by roll pressing. In particular, in the high nickel positive electrode active material system, the formation of gel in the slurry can be further inhibited, thereby further improving the high temperature cycle characteristics of the electrochemical device.
[0080] In an embodiment of the present invention, the adhesive having formula (A) can be prepared by the following preparation method.
[0081] A 25 L reaction vessel is evacuated and nitrogen gas is introduced to replace the oxygen gas. Then, 18 kg of deionized water, 200 g of a 5% sodium perfluorooctanoate solution, and 80 g of paraffin (melting point 60°C) are first added to the reaction vessel, the stirring speed is adjusted to 130 rpm / min, and the temperature of the reaction vessel is increased to 85°C.
[0082] Vinylidene fluoride monomer, tetrafluoroethylene monomer, hexafluoropropylene monomer, and polyvinylpyrrolidone monomer are added in the appropriate ratio to a reactor having a reactor pressure of 5.0 MPa, and then 1.15 g of dioctyl peroxydicarbonate as an initiator is added to carry out a polymerization reaction.
[0083] Then, vinylidene fluoride monomer is added to maintain the pressure of the kettle at 5.0MPa, and 0.01g of initiator is added at 10min batch intervals, and chain transfer agent HFC-4310 is added in 4 batches at conversion rates of 20%, 40%, 60% and 80%, with 5g added each time, and a total of 5kg of vinylidene fluoride monomer is added to the reaction.
[0084] The reaction is continued until the internal pressure of the reaction vessel is reduced to 4.0 MPa. After the reaction time reaches 140 minutes, the vessel is vented and the material is collected. After centrifugation, washing and drying, the adhesive having the formula (A) is obtained.
[0085] In some embodiments of the present invention, the binder comprises: (I) the weight average molecular weight Mw of the binder satisfies 900,000≦Mw≦1,200,000; (II) the weight average molecular weight Mw and the number average molecular weight Mn of the binder satisfy 1.8≦Mw / Mn≦2.4; Satisfy at least one of the characteristics.
[0086] In the above embodiment, the binder satisfies at least one of (I) and (II), and thereby can contribute to the dispersion of the slurry components such as the conductive agent and the positive electrode active material, suppress the formation of gel, and further reduce the occurrence of abnormal aggregation between the components. In particular, in a high nickel positive electrode active material system, the formation of gel in the slurry can be further suppressed, thereby further improving the high temperature cycle characteristics of the electrochemical device.
[0087] In some embodiments of the present invention, the weight percentage X of the binder satisfies 0.5%≦X≦3% with respect to the weight of the positive electrode active material layer.
[0088] In the above embodiment, when the weight percentage X of the binder is within the above appropriate range, the binding strength between the positive electrode active material layer and the positive electrode current collector is increased, and the stability of the positive electrode active material layer is improved.
[0089] In another embodiment of the present invention, the weight percentage X of the binder satisfies 0.7%≦X≦1.5%.
[0090] In some examples, the weight percentage of binder X can be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, or 3%.
[0091] In some embodiments of the present invention, the positive electrode active material layer further includes a conductive agent, which can contribute to improving the electron conduction ability of the positive electrode piece. Exemplarily, the conductive agent is at least one selected from a carbon-based material, a metal-based material, a conductive polymer, and a mixture thereof. Exemplarily, the carbon-based material is selected from carbon black, acetylene black, ketjen black, carbon fiber, carbon nanotube, and any combination thereof. The metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum, and silver. The conductive polymer is a polyphenylene derivative.
[0092] In some embodiments of the present invention, the binding strength F of the positive electrode active material layer satisfies 10 N / m≦F≦40 N / m.
[0093] In the above embodiment, the binder can contribute to the adhesive strength F of the positive electrode active material layer satisfying the above-mentioned relationship, which is advantageous for meeting the adhesive strength requirement when the positive electrode pieces are processed; at the same time, it can slow down the increase rate of the expansion rate of the positive electrode pieces during cycling, so that the electrochemical device has better high-temperature cycling properties.
[0094] The binding strength in the above examples can be measured by the following method. (1) After drying, take a piece of pole and cut it with a blade into a sample 30 mm wide and 100 mm to 160 mm long. (2) A special double-sided tape is attached to a steel plate, the double-sided tape being 20 mm wide and 90 mm to 150 mm long. (3) Attach the sample to the double-sided tape and align it with the double-sided tape, with the measurement surface facing down. (4) A paper tape whose width is the same as that of the sample and whose length is 80 mm longer than that of the sample is inserted under the sample and fixed in place with crepe masking tape to obtain a measurement sample. (5) Turn on the tensioning machine (brand is Sansi, model number is Instron 3365), make the indicator light on, and adjust the limit block to the appropriate position. (6) The measurement sample is fixed on the measurement table, the paper tape is folded upward and fixed with a jig, and the paper tape is pulled at a speed of 10 mm / min. The measurement range is 0 mm to 40 mm. The paper tape is pulled from 90° to separate the positive electrode active material layer attached to the surface of the double-sided tape from the positive electrode current collector, and this is continued until the measurement is completed. (7) Follow the software guide to save the test data, i.e., obtain the adhesion data between the positive active material layer and the positive current collector. After the measurement is completed, take out the sample and close the device.
[0095] The positive electrode pieces in the present invention can be prepared according to the general method in the art, for example, by dispersing and mixing the active material, conductive material and adhesive in N-methylpyrrolidone (NMP) to form a uniform positive electrode slurry, coating the positive electrode slurry on a positive electrode current collector, drying, cold pressing, cutting, slitting and redrying to obtain the positive electrode pieces.
[0096] In some embodiments of the present invention, the electrochemical device further comprises a negative electrode piece, a separator, and an electrolyte.
[0097] The negative electrode piece includes a negative electrode current collector and a negative electrode active material layer provided on at least one surface of the negative electrode current collector. As can be understood, the negative electrode piece may have a negative electrode active material layer provided on one surface of the negative electrode current collector, or may have a negative electrode active material layer provided on both surfaces of the negative electrode current collector, and the embodiment of the present invention is not particularly limited thereto.
[0098] The negative electrode current collector may be a metal foil or a porous metal plate, for example, a foil or a porous plate of a metal such as copper, nickel, titanium, iron, etc., or an alloy thereof. In some embodiments of the present invention, the negative electrode current collector is a copper foil.
[0099] In the present invention, the type of the negative electrode active material in the negative electrode active material layer is not particularly limited and can be selected as necessary. For example, other negative electrode active materials include natural graphite, artificial graphite, mesocarbon microbeads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, SiO, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO 2 , spinel structure Li 4 Ti 5 O 12 , Li-Al alloys, but is not limited to these.
[0100] In some embodiments of the present invention, the negative electrode active material layer further includes a binder, which may be at least one selected from styrene butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0101] In some embodiments of the present invention, the negative electrode active material layer further includes a conductive agent, and the conductive agent may be at least one selected from superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0102] In some embodiments of the present invention, the negative electrode active material layer may further include other auxiliary agents, such as a thickener (eg, sodium carboxymethylcellulose (CMC-Na)).
[0103] However, the present invention is not limited to the materials mentioned above, and the anode pieces of the present invention may use other known materials used as anode active materials, conductive agents, binders and thickeners.
[0104] The negative electrode piece in the present invention can be prepared according to the general method in the art, for example, disperse the negative electrode active material, conductive agent, binder and thickener in a solvent, the solvent can be N-methylpyrrolidone (NMP) or deionized water, form a uniform negative electrode slurry, coat the negative electrode slurry on a negative electrode current collector, dry and cold press to obtain a negative electrode active material layer, and obtain a negative electrode piece.
[0105] The separator is provided between the positive and negative electrodes, and serves mainly to prevent short-circuiting between the positive and negative electrodes and to allow active ions to pass through. The present invention does not particularly limit the type of separator, and any known porous structure separator having good chemical and mechanical stability can be selected.
[0106] In some embodiments of the present invention, the separator may be made of one or more materials selected from, but not limited to, glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. Optionally, the separator may be made of polyethylene and / or polypropylene. The separator may be a monolayer film or a multilayer composite film. When the separator is a multilayer composite film, the materials of each layer may be the same or different. In other embodiments of the present invention, the separator may further include a ceramic coating layer and a metal oxide coating layer.
[0107] In an electrochemical device, the electrolyte is a carrier for transporting ions and can play a role in conducting ions between the positive and negative electrode pieces, thereby ensuring advantages such as good cycle characteristics of the electrochemical device.
[0108] In some embodiments of the present invention, the electrolyte comprises an organic solvent, a lithium salt, and optional additives, and the types of the organic solvent, the lithium salt, and the additives are not specifically limited and can be selected as needed.
[0109] In some embodiments of the present invention, the lithium salt is lithium hexafluorophosphate (LiPF6 ), lithium tetrafluoroborate (LiBF 4 ), lithium perchlorate (LiClO 4 ), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluoro(oxalato)borate (LiDFOB), lithium bis(oxalato)borate (LiBOB), lithium difluorophosphate (LiPO 2 F 2 ), lithium difluorobis(oxalato)phosphate (LiDFOP), and lithium tetrafluoro(oxalato)phosphate (LiTFOP). The lithium salt may be used alone or in combination of two or more.
[0110] In some embodiments of the present invention, the organic solvent comprises at least one selected from ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS), and diethyl sulfone (ESE). The organic solvents may be used alone or in combination of two or more kinds.
[0111] In some embodiments of the present invention, the additive may include a negative electrode film-forming additive, a positive electrode film-forming additive, and may further include an additive that can improve a specific performance of the battery, such as an additive that improves the overcharge characteristics of the battery, an additive that improves the high temperature or low temperature characteristics of the battery, etc.
[0112] In some examples, the additive comprises at least one selected from fluoroethylene carbonate (FEC), vinylene carbonate (VC), vinyl ethylene carbonate (VEC), ethylene sulfate (DTD), 1,3-propylene sulfate, ethylene sulfite (ES), 1,3-propane sultone (PS), 1-propene 1,3-sultone (PST), sulfonate cyclic quaternary ammonium salts, succinic anhydride, succinonitrile (SN), adiponitrile (AND), tris(trimethylsilyl)phosphate (TMSP), and tris(trimethylsilyl)borate (TMSB).
[0113] The electrolyte can be prepared according to a general method in the art. For example, an organic solvent, a lithium salt, and an optional additive can be mixed uniformly to obtain an electrolyte. The order of addition of each material is not particularly limited. For example, a lithium salt and an optional additive can be added to an organic solvent and mixed uniformly to obtain an electrolyte. Alternatively, a lithium salt can be added to an organic solvent first, and then an optional additive can be added to an organic solvent and mixed uniformly to obtain an electrolyte.
[0114] In some embodiments of the present invention, the positive electrode pieces, the negative electrode pieces and the separator may be formed into an electrode assembly by a winding process or a stacking process.
[0115] The electrochemical device according to the embodiment of the present invention further includes an exterior for sealing the electrode assembly and the electrolyte. In some embodiments of the present invention, the exterior may be a hard case, such as a hard plastic case, an aluminum case, a steel case, or the like, or a soft pack, such as a pouch-type soft pack. The material of the soft pack may be plastic, such as at least one selected from polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).
[0116] The embodiment of the present invention is not particularly limited with respect to the shape of the electrochemical device, which may be cylindrical, rectangular, or any other shape. For example, FIG. 1 shows an electrochemical device with a rectangular structure as an example.
[0117] In some embodiments of the present invention, referring to FIG. 2, the exterior may include a case 51 and a top cover assembly 53. Here, the case 51 includes a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate surround and form a receiving cavity. The case 51 has an opening communicating with the receiving cavity, and the top cover assembly 53 is provided to cover the opening to close the receiving cavity. The positive electrode piece, the negative electrode piece and the separator may form an electrode assembly 52 through a winding process or a stacking process. The electrode assembly 52 is sealed in the receiving cavity. The electrolyte permeates the electrode assembly 52. The number of electrode assemblies 52 included in the electrochemical device 5 may be one or more, and those skilled in the art may select according to specific practical needs.
[0118] After the electrolyte has permeated the electrode assembly, the assembly is subjected to steps such as vacuum sealing, standing, formation, and exhaust molding to obtain an electrochemical device.
[0119] electronic equipment A second aspect of the present invention provides an electronic device, the electronic device comprising the electrochemical device provided in the first aspect of the present invention. The electrochemical device provided by the present invention has good high-temperature cycle characteristics and high energy density, and therefore the electronic device provided by the present invention has good high-temperature cycle characteristics.
[0120] The embodiments of the present invention are not particularly limited to electronic devices and can be applied to any electronic devices known in the prior art. In some embodiments of the present invention, the electronic devices include, but are not limited to, notebook computers, pen-input computers, mobile computers, electronic book players, mobile phones, portable facsimiles, portable copy machines, portable printers, stereo headsets, video recorders, LCD televisions, portable cleaners, portable CD players, minidisks, walkie-talkies, electronic notebooks, calculators, memory cards, portable tape recorders, radios, backup power supplies, motors, automobiles, motorcycles, power-assisted bicycles, bicycles, lighting equipment, toys, game consoles, watches, power tools, flashlights, cameras, large household storage batteries, and lithium-ion capacitors.
[0121] The following examples will more fully describe the disclosed subject matter of the present invention, and these examples are for illustrative purposes only, since it will be apparent to those skilled in the art that various modifications and variations within the scope of the present invention may be made. Unless otherwise specified, all parts, percentages, and ratios described in the following examples are by weight, all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further treatment, and the equipment used in the examples is commercially available.
[0122] In the following examples, for convenience of explanation, the electrochemical device and the manufacturing method thereof will be described in detail using a lithium ion secondary battery as an example of the electrochemical device.
[0123] Example 1-1 Preparation of positive electrode pieces Conductive carbon black and binder were mixed in a certain ratio, and NMP was added and mixed with stirring to produce a conductive adhesive liquid (solid content 7%). The positive electrode active material, lithium nickel cobalt manganese oxide (NCM), was added to the conductive adhesive solution and stirred under the action of a vacuum mixer until the system became homogeneous, obtaining a positive electrode slurry with a solid content of about 75%. Here, the mass ratio of NCM, conductive carbon tubes, and binder was 97:1:2. This positive electrode slurry was applied to an aluminum foil having a thickness of 10 μm, and the foil was dried, cold pressed, cut, and tab-welded to obtain a positive electrode piece.
[0124] Preparation of negative electrode pieces Artificial graphite, styrene butadiene rubber, and sodium carboxymethyl cellulose were mixed with deionized water and an auxiliary in a mass ratio of 96:2:2, and stirred uniformly to obtain a negative electrode slurry. This negative electrode slurry was applied to a 12 μm copper foil, which was then dried, cold pressed, cut, and tab-welded to obtain a negative electrode piece.
[0125] Preparation of electrolyte EC, PC and DEC (weight ratio 1:1:1) were mixed in a dry argon gas atmosphere and LiPF 6 and mixed uniformly to form a base electrolyte. 6 The concentration was 1.15 mol / L.
[0126] Preparation of the separator A polyethylene (PE) porous polymer film was used as the separator.
[0127] Preparation of lithium-ion secondary batteries The positive electrode piece, the separator, and the negative electrode piece were wound in that order to form an electrode assembly, the electrode assembly was placed on an exterior foil, an electrolyte was injected into the exterior foil to permeate the electrode assembly, and a lithium ion secondary battery was obtained through processes such as sealing, formation, and shaping.
[0128] Examples 1-2 to 1-6 The preparation method was similar to that of Example 1-1, except that some parameters of the positive electrode pieces were different. See Table 1 for details.
[0129] Comparative Examples 1-1 to 1-4 The preparation method was similar to that of Example 1-1, except that some parameters of the positive electrode pieces were different. See Table 1 for details.
[0130] Examples 2-1 to 2-7 The preparation method was similar to that of Example 1-1, except that some parameters of the positive electrode pieces were different. See Table 2 for details.
[0131] Examples 3-1 to 3-9 The preparation method was similar to that of Example 1-1, except that some parameters of the positive electrode pieces were different. See Table 3 for details.
[0132] Examples 4-1 to 4-8 Except for some differences in the parameters of the positive electrode pieces, the preparation method was similar to that of Example 1-1. See Table 4 for details.
[0133] Examples 5-1 to 5-5 The preparation method was similar to that of Example 1-1, except that some parameters of the positive electrode pieces were different. See Table 5 for details.
[0134] Measuring part 1) Measurement of the surface density of the positive electrode active material layer The positive electrode piece coated with the positive electrode active material layer was punched out into 10 small circular pieces, each with a surface area of 1540.25 mm 2 The punched positive electrode pieces are weighed and the average value is taken to obtain the mass m1. Next, the positive electrode current collector is taken and punched into 10 small circular pieces in the same manner. These pieces are weighed on a balance and the average value is taken to obtain the mass m2. The areal density = (m1 - m2) / 1540.25 mm 2 It was.
[0135] 2) Measurement of the compressed density of the positive electrode active material layer The lithium-ion secondary battery to be measured after discharge was disassembled, the positive electrode piece was removed, and the positive electrode piece was immersed in DMO (dimethyl oxalate) for 30 minutes to remove the electrolyte and by-products from the surface of the positive electrode piece. The positive electrode piece was then dried for 4 hours in a draft chamber, and the thickness H of the positive electrode active material layer on the positive electrode piece was measured using a micrometer with an accuracy of 0.1 μm. 1 Then, a unit area of the positive electrode active material layer is scraped off from the positive electrode piece with a doctor blade, and the mass (m3) of the positive electrode active material layer per unit area on the positive electrode piece is measured with a balance. The compressed density of the positive electrode active material layer is then measured. 1 The calculation was based on the following:
[0136] 3) Positive electrode active material D v 50, D v 10. D v 99 measurements (1) Starting up the instrument: First, the sample injection system of the laser diffraction / scattering particle size distribution analyzer (Master Sizer 3000) was started up, then the optical path system and computer were started up, and the instrument was preheated for 30 minutes. (2) Cleaning of the sample injection system: Fill the sample injector with water, adjust the rotation speed to maximum, clean for 5 s, and then adjust the rotation speed to 0. Repeat cleaning three times to ensure the cleaning of the sample injector. (3) Enter the “Manual Measurement” interface and set the material name, refractive index, material type, measurement time, number of measurements, etc. in order. (4) Click “start” to collimate the light and measure the background light. (5) Prepare a sample by dispersing the positive electrode active material in an aqueous solution (10 mL), and add the sample to the sample pool. The light shielding degree increases with the amount of sample added. When the light shielding degree increases to 8% to 12%, stop the sample injection and wait until the light shielding degree becomes stable (generally does not fluctuate for 30 s), then click "start" to start measuring the particle size, and after the measurement is completed, D v 50, D v 10. D v I got 99. (6) Measure three parallel samples and v 50, D v 10. Dv The 99 average values were calculated.
[0137] 4) Thickness H of the positive electrode current collector 2 Measurement The thickness H of the positive electrode current collector is measured with a micrometer with an accuracy of 0.1 μm. 2 was measured.
[0138] 5) Measurement of weight average molecular weight Mw and number average molecular weight Mn of binder The molecular weight and molecular weight distribution were measured in accordance with GB / T 21863-2008 gel permeation chromatography using ultra-fast polymer chromatography: ACQUITY APC, and detector: ACQUITY refractive index detector. The measurement procedure is as follows. (1) Start-up preheating: The chromatography column and pipeline were installed, the console, measurement power supply, etc. were turned on in sequence, and the measurement software Empower was opened. (2) The parameters were set: sample injection volume: 0 μL to 50 μL (determined according to the sample concentration); pump flow rate: 0.2 mL / min; mobile phase: 30 mol / L LiBr in NMP; seal wash: isopropanol; precolumn: PL gel 10 μm MiniMIX-B Guard (dimensions: 50 mm × 4.6 mm × 2); analytical phase: PL gel 10 μm MiniMIX-B (dimensions: 250 mm × 4.6 mm); standard: polystyrene set; run time: 30 min; detector: ACQUITY differential refractive index (RI) detector; column oven temperature: 90 °C; detector temperature: 55 °C. (3) Sample measurement: a. Placement of standard sample and measurement sample: Weigh out 0.002g~0.004g of each standard sample / measurement sample and add it to 2mL of mobile phase liquid to prepare a 0.1%~0.5% mixed standard solution, and leave it in the refrigerator for >8h. b. Measurement of standard solution / sample: Edit the sample group to be measured, select the established sample group method, and after the baseline is stabilized, click on the execution queue and start the measurement sample. (4) Data processing: Based on the relationship between retention time and molecular weight, a calibration curve was established using a chemical workstation, and integral quantification was performed on the sample spectrum, and the chemical workstation automatically generated the molecular weight and molecular weight distribution results.
[0139] 6) Diameter of the coagulation region D 0 and measurement of number density per unit area (1) After drying, a pole piece was taken and a sample 5 cm wide and 5 cm long was cut out with a blade and fixed to the microscope measurement stage. (2) The microscope measuring device was started, and the measuring magnification was adjusted to X100, and was adjusted until the interface became clear. (3) Start the measurement, select an observation area of 1.0 cm × 1.0 cm as the observation area, count the number of white agglutination areas in the observation area, and measure the maximum diameter of the agglutination area to obtain D 0 was recorded as.
[0140] 3 and 4 show SEM images of the positive electrode pieces of Example 1 and Comparative Example 1, respectively.
[0141] 7) Measuring the resistance of the positive pole piece Measurements were made using a resistance meter, and the specific method is as follows. The power supply of the device was kept at 220 V, and the air pressure was set to be greater than 0.7 MPa. When the battery was in a fully discharged state, the positive electrode piece was removed, and the cut positive electrode piece (60 x 80 mm) was placed horizontally on the sample mounting stage. Next, the sample mounting stage was placed in the measurement cavity of the device, and measurement was started. Here, the measurement air pressure was set to "0" throughout the entire measurement process.
[0142] 8) Capacity retention rate measurement The measurement environment temperature was 45°C, and the lithium-ion battery after formation was charged at a constant current charging stage current of 1.3C until the cut-off voltage reached 4.5V, then constant voltage charging was performed, and charging was stopped until the cut-off current reached 0.05C. After the battery was fully charged, it was left to stand for 5 minutes, and then discharged at a current of 1.0C until the voltage reached 3.0V, which was considered as one charge-discharge cycle process. After repeating such charge-discharge cycles 500 times, the cycle capacity retention rate was calculated by dividing the discharge capacity after the 500th cycle by the discharge capacity of the first cycle.
[0143] 9) Measurement of thickness expansion of lithium-ion secondary batteries: The thickness of the lithium-ion secondary battery was measured using a PPG plate thickness meter. The thickness expansion rate of the lithium-ion secondary battery = (fully charged thickness after cycling - first fully charged thickness) / first fully charged thickness x 100%.
[0144] Table 1 shows the relevant parameters (D v 99 / H 1 , D 0 , number density) and their measurement results are shown.
[0145] [Table 1]
[0146] As can be seen from Table 1, when comparing the measurement results of Examples 1-1 to 1-6 and Comparative Examples 1-1 to 1-4, in the electrochemical device provided by the examples of the present invention, the thickness H 1 D of the positive electrode active material v The ratio of 99 is 0.5≦D v 99 / H 1 ≦0.9 and the diameter D of the bright spot on the surface of the positive electrode active material layer observed by a scanning electron microscope 0 is 20 μm, or the number density per unit area of the agglomerated region larger than 20 μm is 5 pieces / cm 2 or 5 pieces / cm 2The smaller size contributes to achieving both rate characteristics and high-temperature cycle characteristics of the electrochemical device.
[0147] Table 2 shows the relevant parameters (D v 50, D v 10. D v 50 / D v 10) and the measurement results are shown below.
[0148] [Table 2]
[0149] As can be seen from Table 2, when the measurement results of Examples 2-1 to 2-5 and 2-7 are compared with those of Example 2-6, the particle size distribution of the positive electrode active material is 1.0≦D v 50 / D v When the ratio satisfies 10≦2.5, the fracture of the positive electrode active material can be reduced, and the resistance of the positive electrode pieces and the expansion rate of the electrochemical device can be further reduced, so that the high temperature cycle characteristics of the electrochemical device can be further improved.
[0150] Table 3 shows the relevant parameters (D v 99, H 1 ), related parameters of the positive electrode current collector (H 2 , H 2 / D v 99, H 1 / H 2 ) and the measurement results are shown.
[0151] [Table 3]
[0152] As can be seen from Table 3, when the measurement results of Examples 3-2, 3-3, 3-5 and 3-8 are compared, the particle size distribution D of the positive electrode active material v 99 and H 2 / D vWhen 99 is within an appropriate range, it can contribute to reducing the resistance of the positive electrode piece and the expansion rate of the electrochemical device, and can improve the high-temperature cycle characteristics of the electrochemical device.
[0153] As can be seen from a comparison of the measurement results of Examples 3-3 and 3-4, the thickness H 1 and H 1 / H 2 When the content of the positive electrode piece is within an appropriate range, it is possible to contribute to reducing the resistance of the positive electrode piece and the expansion rate of the electrochemical device, thereby improving the high-temperature cycle characteristics of the electrochemical device.
[0154] As can be seen from a comparison of the measurement results for Examples 3-2, 3-6, and 3-7, the thickness H 2 and H 1 / H 2 When the content of the positive electrode piece is within an appropriate range, it is possible to contribute to reducing the resistance of the positive electrode piece and the expansion rate of the electrochemical device, thereby improving the high-temperature cycle characteristics of the electrochemical device.
[0155] Table 4 lists the measurement results for the positive electrode active materials in Examples 4-1 to 4-8 at different areal densities and compressed densities.
[0156] [Table 4]
[0157] Note: The unit of areal density is mg / 1540.25 mm 2 and The unit of compressed density is g / cm 3 It is.
[0158] As can be seen from Table 4, when the measurement results of Examples 4-1 to 4-4 are compared, the compressed density of the positive electrode active material layer is 3.3 g / cm 3 ~3.7g / cm 3Within this range, the resistance of the positive electrode piece is low and the expansion coefficient of the electrochemical device is low, thereby further improving the high-temperature cycle characteristics of the electrochemical device.
[0159] As can be seen from a comparison of the measurement results of Examples 4-5 to 4-7, the surface density of the positive electrode active material layer was 80 mg / 1540.25 mm 2 ~180mg / 1540.25mm 2 Within this range, the resistance of the positive electrode piece is low and the expansion coefficient of the electrochemical device is low, thereby further improving the high-temperature cycle characteristics of the electrochemical device.
[0160] [Table 5]
[0161] As can be seen from Table 5, in the electrochemical device provided by the embodiments of the present invention, the binder contained in the positive electrode active material layer can effectively suppress the formation of gel, which is advantageous for improving the high-temperature cycle characteristics of the electrochemical device.
[0162] Finally, it should be noted that the above embodiments are used to explain the technical solutions of the present invention, and are not limiting. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art may still modify the technical solutions described in the above embodiments, or make equivalent substitutions to some or all of the technical features, provided that the essence of the corresponding technical solutions does not deviate from the scope of the technical solutions of the embodiments of the present invention through these modifications and substitutions, and all of these should be included in the scope of the claims and specification of the present invention. In particular, the technical features described in the embodiments may be combined in any manner, provided there is no structural contradiction. The present invention is not limited to the specific embodiments disclosed herein, and includes all technical solutions included in the scope of the claims.
Claims
1. 1. An electrochemical device comprising: The positive electrode piece includes a positive electrode current collector and a positive electrode active material layer provided on one or both sides of the positive electrode current collector, The positive electrode active material layer contains a positive electrode active material, The thickness H of the positive electrode active material layer on one side 1 D of the positive electrode active material v The ratio of D to D is 0.5≦D v 99 / H 1 ≦0.9 is satisfied, The diameter D of the bright spot on the surface of the positive electrode active material layer was measured by a scanning electron microscope. 0 is 20 μm or more, and an agglomeration region larger than 20 μm is observed, and the number density of the agglomeration regions per unit area on the surface of the positive electrode active material layer is 5 pieces / cm 2 or 5 pieces / cm 2 Less than Electrochemical equipment.
2. D of the positive electrode active material v 99 is 15 μm≦D v 99≦30 μm, and the thickness H of the positive electrode active material layer on one side is 1 10 μm≦H 1 The electrochemical device of claim 1 , wherein the thickness satisfies ≦35 μm.
3. D of the positive electrode active material v D of the positive electrode active material to 10 v The ratio of 50 is 1.0<D v 50 / D v The electrochemical device according to claim 1 or 2, wherein 10≦2.5 is satisfied.
4. D of the positive electrode active material v D of the positive electrode active material to 10 v The ratio of 50 is 1.0<D v 50 / D v The electrochemical device according to any one of claims 1 to 3, wherein 10≦2.0 is satisfied.
5. 5. The electrochemical device according to claim 1, wherein the positive electrode active material contains a nickel-cobalt-manganese ternary material.
6. 6. The electrochemical device of claim 5, wherein the moles of nickel in the nickel-cobalt-manganese ternary material are equal to or greater than 60% of the total moles of nickel, cobalt and manganese.
7. The thickness H of the positive electrode current collector 2 teeth, I)0.3≦H 2 / D v 99≦1、 I))≦H 1 / 2 ≦.、 III)7μm≦H 2 ≦20μm、 The electrochemical device according to any one of claims 1 to 6, which satisfies at least one of the above.
8. The thickness H of the positive electrode current collector 2 8 μm≦H 2 The electrochemical device according to any one of claims 1 to 7, which satisfies ≦12 μm.
9. The surface density of the positive electrode active material layer is 80 mg / 1540.25 mm 2 ~180mg / 1540.25mm 2 The electrochemical device according to any one of claims 1 to 8,
10. The compressed density of the positive electrode active material layer is 3.3 g / cm 3 ~3.7g / cm 3 The electrochemical device according to any one of claims 1 to 9,
11. The compressed density of the positive electrode active material layer is 3.5 g / cm 3 ~3.65g / cm 3 The electrochemical device according to any one of claims 1 to 10,
12. The positive electrode active material layer further contains a binder, and the binder has a characteristic peak in the corresponding Fourier transform infrared spectrum: 1684 cm -1 The electrochemical device according to any one of claims 1 to 11, comprising:
13. The electrochemical device of claim 12 , wherein the binder comprises a polyvinylidene fluoride copolymer.
14. The binder has a structural formula of formula (A): (VDF)m(TFE)n(HFP)r(PVP)x (A) 14. The electrochemical device according to claim 12 or 13, wherein, in formula (A), VDF is a structural unit of vinylidene fluoride, TFE is a structural unit of tetrafluoroethylene, HFP is a structural unit of hexafluoropropylene, and PVP is a structural unit of polyvinylpyrrolidone, and m, n, r, and x satisfy 0.35≦m≦1, 0≦n≦0.4, 0≦r≦0.2, 0≦x≦0.2, and m+n+r+x=1.
15. An electronic device comprising an electrochemical device according to any one of claims 1 to 14.
Citation Information
Patent Citations
Electrochemical device and electronic device
CN114614106A
Lithium secondary battery
JP2013149370A
Nonaqueous electrolytic secondary battery
JP2013201077A
Lithium ion secondary battery
JP2017152177A
Lithium secondary battery and positive electrode for said battery
WO2011039890A1